Effect of laser parameters and compression ratio on particulate emissions from a laser ignited hydrogen engine. (13th April 2017) - Agarwal, Avinash Kumar; Singh, Akhilendra Pratap; Pal, Anuj
Abstract: Due to stricter emission legislations and rapid depletion of petroleum resources, research efforts are being made to explore advanced combustion concepts as well as alternative fuels for IC engines, in order to sustain transport sector. Amongst numerous potential options, hydrogen has been identified as one of the most promising alternative fuel candidate. Utilization of hydrogen in IC engines is challenging but it can be successfully achieved by applying laser ignition (LI), which is a novel ignition concept. Researchers have proved that LI parameters significantly affect combustion, performance and emissions characteristics of hydrogen fueled engines; however information about its effect on particulate characteristics is not available in open literature. In this experimental study, particulate emissions from a hydrogen fueled engine using different LI parameters namely laser pulse energy (E) and spark timing (ST), and different compression ratios (CR) have been analyzed. Experiments were carried out in a suitably modified single cylinder prototype engine, which is capable of operating on gaseous fuels and has a LI system. Results showed that increasing engine load resulted in higher particulate number concentration. Increasing E led to formation of higher number of nucleation mode particles (NMP) and accumulation mode particles (AMP). Advancing ST led to higher particulate number concentration, which dominated in the NMP regime therefore the count mean diameter (CMD) of particulate remained relatively smaller. At higher CR, slightly higher particulate concentration was another important observation. Particulate number-size distribution showed greater dominance of CR in AMP regime, compared to NMP regime. This study demonstrated that particulate emissions from laser ignited, hydrogen fueled engines can be controlled by selection of optimum laser parameters and CR of the test engine. Highlights: Effect of LI parameters & CR on particulate emissions is investigated. Particulate number concentration increased with increasing load. Increasing laser pulse energy led to higher number of NMPs and AMPs. Advancing spark timing led to higher particulate number concentration. Higher CR also led to slightly higher particulate concentration.